Recent Development of Thermoelectric Polymers and Composites - Yao, Hongyan; Fan, Zeng; Cheng, Hanlin; Guan, Xin; Wang, Chen; Sun, Kuan; Ouyang, Jianyong (Macromolecular rapid communications., 2018)
Thermoelectric materials can be used as the active materials in thermoelectric generators and as Peltier coolers for direct energy conversion between heat and electricity. Apart from inorganic thermoelectric materials, thermoelectric polymers have been receiving great attention due to their unique advantages including low cost, high mechanical flexibility, light weight, low or no toxicity, and intrinsically low thermal conductivity. The power factor of thermoelectric polymers has been continuously rising, and the highest ZT value is more than 0.25 at room temperature. The power factor can be further improved by forming composites with nanomaterials. This article provides a review of recent developments on thermoelectric polymers and polymer composites. It focuses on the relationship between thermoelectric properties and the materials structure, including chemical structure, microstructure, dopants, and doping levels. Their thermoelectric properties can be further improved to be comparable to inorganic counterparts in the near future. Thermoelectric polymers have gained great attention, arising from their merits of low cost, light weight, low or no toxicity, and high mechanical flexibility. This article provides a review on the recent progress of thermoelectric polymers and composites.